Ultraselective Carbon Nanotubes for Photoacoustic Imaging of Inflamed Atherosclerotic Plaques (Adv. Funct. Mater. 37/2021). (9th September 2021) - Gifani, Mahsa; Eddins, Devon J.; Kosuge, Hisanori; Zhang, Yapei; Paluri, Sesha L. A.; Larson, Timothy; Leeper, Nicholas; Herzenberg, Leonore A.; Gambhir, Sanjiv Sam; McConnell, Michael V.; Ghosn, Eliver E. B.; Smith, Bryan Ronain
Abstract : Ultraselective Carbon Nanotubes Vulnerable atherosclerotic plaques can result in heart attacks. Inflammation, particularly inflammatory monocytes/macrophages, characterizes such plaques. In article number 2101005, Eliver E. B. Ghosn, Bryan Ronain Smith, and co‐workers present single‐walled carbon nanotubes' unprecedented selectivity to inflammatory monocytes/macrophages that infiltrate plaques, allowing specific detection of inflamed plaques using photoacoustic imaging (laser in, ultrasound out). This highly selective strategy, confirmed by high‐dimensional flow cytometry, can accurately identify and diagnose inflamed atherosclerotic lesions.